ONLINE ESP TEACHING DURING THE COVID 19 PANDEMIC: STUDENTS’ VOICES - Latifa Ika Sari; Ria Hermina Sari (University of Kuningan, 2022)
This study was aimed to evaluate the online ESP teaching in a Maritime Polytechnic in Indonesia, focusing on the teaching media used by the Maritime English lecturers: the Learning Management System, Zoom, and YouTube. 195 students of the Nautical Studies Department were involved in completing a questionnaire. 12 of them were involved in a Focus Group Interview to obtain more detailed and comprehensive information. Thematic analysis was used to analyze data and a thematic map was presented to illustrate the relationship between the themes. The findings of this study indicate that most students perceived the teaching media used by the lecturers in the online Maritime English classroom were beneficial. However, each teaching medium was reported to have its advantages and disadvantages. If combined appropriately, they can facilitate students’ language learning. It is suggested that the lecturers explore various teaching media and arrange appropriate pacing in their teaching practices. The lecturers also need to prepare their lessons well before teaching to ensure that students can receive the best online learning experience.